The Impact of Social Media and Attachment Style in Long-Distance Intimate Overall Relationship Satisfaction and Conflict - Yan, Yuying (Transactions on Social Science, Education and Humanities Research, 2024)
Social media has become a prevalent channel for communication in the modern era. Long-distance couples must keep or improve their overall level of relationship satisfaction. Most earlier studies examined how an individual’s attachment types and use of social networking sites (SNS) affect the evaluation of long-distance relationship satisfaction separately. there is insufficient data for identifying how satisfaction is affected when subjective (attachment styles) and objective (social media) factors are combined. This study aims to examine the shortcomings of past studies. According to this analysis, the couple’s assessment of how satisfied they are with their relationship and their personal decisions made on social media are moderated by attachment style. Individuals with diverse attachment styles might disclose themselves in different ways, require varying degrees of intimacy, and view love relationships in various manners. Additionally, this article, including various methodological and hypothesis suggestions, will lay the groundwork for future research.